KEY INDICATORS OF CLUSTERIZATION POTENTIAL IN REGIONAL TOURISM - Maria GRITSAY; Evgenia KULAGINA; Olga LUKINA; Olga PRONCHEVA (Geo Journal of Tourism and Geosites, 2018)
The research is aimed at proposing a system of clustering the tourist potential of a territory. The results are of interest for experts dealing with regional tourism development from the point of view of cluster approach. The theoretical part defines a tourist cluster as a network of the subjects of the regional tourist market, formed to promote the competitive product between the businesses and to preserve the vertical and horizontal inter-cluster competition. The documents determining the tourism development strategy in the Russian Federation are analyzed, and the results show a range of cluster initiative support policy distributions with the development of the regional tourism.